Chloroform Inactivation of Reovirus Hemagglutinins - Rozee, K. R. (1967)
The hemagglutinin of all three types of reovirus was inactivated by chloroform with little or no diminution in virus infectivity. Albumin and other proteins protected the hemagglutinin from inactivation by chloroform. When crude reovirus suspensions were centrifuged in a sucrose density gradient, two hemagglutinin fractions were collected. The fraction which sedimented more rapidly contained the bulk of infectious virus, but both lost hemagglutinin activity when extracted with chloroform. Ether extraction of the fractions did not reduce either the infectivity or hemagglutinin titre.